2022
DOI: 10.1021/jacsau.2c00526
|View full text |Cite
|
Sign up to set email alerts
|

Transferable Deep Learning Potential Reveals Intermediate-Range Ordering Effects in LiF–NaF–ZrF4 Molten Salt

Abstract: LiF−NaF−ZrF 4 multicomponent molten salts are promising candidate coolants for advanced clean energy systems owing to their desirable thermophysical and transport properties. However, the complex structures enabling these properties, and their dependence on composition, is scarcely quantified due to limitations in simulating and interpreting experimental spectra of highly disordered, intermediate-ranged structures. Specifically, sizelimited ab initio simulations and accuracy-limited classical models used in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 46 publications
1
20
0
1
Order By: Relevance
“…The prepeak manifested consistently across all simulations featuring UF 4 and ThF 4 additives, but it remained absent in all simulations of the pure system. Medium-range ordering has also been reported in the literature for similar molten salt systems: Li et al 12 identified cluster formation in NaCl with the addition of UCl 3 and UCl 4 , while Chahal et al 29 observed the formation of networks in LiF−NaF upon the introduction of ZrF 4 .…”
Section: ■ Results and Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The prepeak manifested consistently across all simulations featuring UF 4 and ThF 4 additives, but it remained absent in all simulations of the pure system. Medium-range ordering has also been reported in the literature for similar molten salt systems: Li et al 12 identified cluster formation in NaCl with the addition of UCl 3 and UCl 4 , while Chahal et al 29 observed the formation of networks in LiF−NaF upon the introduction of ZrF 4 .…”
Section: ■ Results and Discussionmentioning
confidence: 58%
“…A medium-range order has been investigated for decades in metallic melts, ionic liquids, and protein solutions. These structures are linked to the emergence of a prepeak in the structure factor, indicating spatial correlations beyond the length scale represented by the main structure factor peak. These extended correlations seem to have an impact on the thermophysical and transport properties of the liquid, though the exact relationship is not entirely clear. In polymers, for instance, it is well-established that the structure and weight of the chain influence viscosity, , with viscosity increasing as molecular weight and chain length increase. In contrast, for molten salts and liquids in general, there is not a prevailing theory relating viscosity to their structure.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating properties such as solubility, viscosity, diffusivity, and conductivity, and connecting them directly to ion exchange and speciation, is out of the scope of this AIMD study. However, in the future, through the development of accurate machine learning 30,57,58 interatomic interaction potentials trained on ab initio forces and energies, accessing both large length scales and long simulation times will be possible. This will help establish the property-speciation-ion exchange relations, providing a means to enhance the performance of the high-temperature energy storage and production technologies.…”
Section: Discussionmentioning
confidence: 99%
“…36 At present, the DPMD simulations have been successfully performed on molten chlorides 37–39 and fluorides. 40,41…”
Section: Introductionmentioning
confidence: 99%
“…36 At present, the DPMD simulations have been successfully performed on molten chlorides [37][38][39] and fluorides. 40,41 In this work, LaF 3 as a representative lanthanide fluoride is added into molten Flibe eutectic salt to investigate the macroscopic properties and microscopic structure of molten mixtures. Firstly, diverse FPMD simulations of molten Flibe + LaF 3 are conducted at 823 K with small simulation cells under the complete consideration of the position of La.…”
Section: Introductionmentioning
confidence: 99%